TRANSFORMASI LIMBAH GEOTERMAL MENJADI SUMBER SILIKA: TINJUAN POTENSI APLIKASI INDUSTRI - Khadafi, Rama; Ojahan R, Tumpal (Bhinneka Multidisiplin Journal, 2025)
Indonesia's vast geothermal potential (23.7 GW, 40% of global reserves) faces operational challenges from silica scaling amorphous SiO₂ deposition in pipelines and equipment. This review repositions scaling from a waste problem to a strategic resource, leveraging its high silica content (88–97%), amorphous structure, and unique morphology. Through systematic literature analysis, we identify two key scaling formation pathways (heterogeneous botryoidal layers and homogeneous 3D aggregates) influenced by temperature, pH, and flow dynamics. Silica scaling exhibits high surface area (up to 50 m²/g) and mesoporosity (2–50 nm), enabling extraction via alkali-acid processing into functional materials. Impurities (Fe, Al, Ca) are transformed into value-added components for catalysts, geopolymers, and composites. We map industrial applications adsorbents, ceramic fillers, and nanostructured materials based on material properties and local scalability. This circular economy approach reduces operational costs while creating new revenue streams. Key barriers include standardization gaps and supply chain integration, necessitating industry-geothermal sector collaboration for sustainable implementation in Indonesia.